Pengaruh Metoda Mengajar Khusus, Praktik Lapangan Kependidikan dan Efikasi Diri terhadap Kesiapan Menjadi Guru - Aditya Putra; Ahyanuardi Ahyanuardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to determine the effect of special teaching methods, educational field practices and self-efficacy on readiness to become a teacher for students of the 2018 Electrical Engineering Education study program, Padang State University. This research method uses a quantitative approach, meaning that all information or data is realized in the form of numbers and analyzed based on statistical regression analysis. The respondents in this study were students of the 2018 PTE study program who had carried out PLK. The data collection technique used a questionnaire with scoring using a multilevel scale that had been validated by an expert lecturer at the Department of Electrical Engineering before being tested and distributed to respondents. In this study, the number of respondents was 46 people. The data analysis technique used multiple linear regression analysis and hypothesis testing using t-test to determine the partial effect between independent and dependent variables and f-test to determine the simultaneous effect between independent and dependent variables. The results of this study indicate that (1) Special Teaching Methods have no effect on readiness to become a teacher (2) Educational Field Practice has a positive and significant effect on readiness to become a teacher (3) Self-Efficacy has a positive and significant effect on readiness to become a teacher (4) There is a positive influence and the significance of Special Teaching Methods, Educational Field Practices and Self-Efficacy together on readiness to become teachers.